2012
DOI: 10.1074/jbc.m112.346437
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Pink1 Gene in Vivo Sensitizes Dopamine-producing Neurons to 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and Can Be Rescued by Autosomal Recessive Parkinson Disease Genes, Parkin or DJ-1

Abstract: Mutations in the mitochondrial PTEN-induced kinase 1 (Pink1) gene have been linked to Parkinson disease (PD). Recent reports including our own indicated that ectopic Pink1 expression is protective against toxic insult in vitro, suggesting a potential role for endogenous Pink1 in mediating survival. However, the role of endogenous Pink1 in survival, particularly in vivo, is unclear. To address this critical question, we examined whether down-regulation of Pink1 affects dopaminergic neuron loss following 1-methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 50 publications
(93 reference statements)
1
60
0
Order By: Relevance
“…Importantly, UCP-2 is neuroprotective in both Drosophila and mouse models of PD [40,41]. It has recently been shown that PINK1 -/- mice are more sensitive to 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced dopamine neuron loss [42], although it has not been investigated whether impaired expression of UCP-2 was involved.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, UCP-2 is neuroprotective in both Drosophila and mouse models of PD [40,41]. It has recently been shown that PINK1 -/- mice are more sensitive to 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced dopamine neuron loss [42], although it has not been investigated whether impaired expression of UCP-2 was involved.…”
Section: Discussionmentioning
confidence: 99%
“…Haque et al showed that PINK1 knockout mice have increased susceptibility to the ROS-generating PD toxin MPTP. 114 This group rescued PINK1 deficient mice by overexpressing Parkin or DJ-1 suggesting PINK1 lies upstream of these factors in a common pathway. Additionally, Akundi et al showed repression of PINK1 expression results in heightened susceptibility to inflammatory response-mediated DA neuron loss.…”
Section: Pink1 (Park6)mentioning
confidence: 97%
“…PINK-1 mutant flies share a similar phenotype as parkin mutants [152, 328], and over-expression of parkin can rescue the mitochondrial defects of PINK-1 mutant flies [152, 328, 329]. Parkin can also protect PINK1 deficient mice against MPTP [330]. Mechanistically, PINK1 and parkin work together for the selective clearance of damaged mitochondria through mitophagy [303].…”
Section: The Role Of Pd-related Proteins In Oxidative Stressmentioning
confidence: 99%
“…Over-expression of DJ-1 and PINK1 synergistically protects SH-SY5Y cells against MPTP-induced cell death; this effect is lost in the presence of A39S mutant DJ-1 and P399L mutant PINK1 [332]. In vivo , viral vector mediated expression of DJ-1 mitigates the increased sensitivity of PINK1 deficient mice to MPTP [330]. Similarly, ubiquitous up-regulation of DJ-1 in Drosophila can ameliorate the phenotype of PINK1 deletion [333].…”
Section: The Role Of Pd-related Proteins In Oxidative Stressmentioning
confidence: 99%